The extent of ethical leadership among youth: the case of a developing country - Nazahah Rahim,; Nurwati A. Ahmad-Zaluki, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Ethical leadership is a form of leadership where individuals demonstrate acceptable and appropriate conducts in every aspect of their life. However, in Malaysia this form of leadership seems to be lacking as one of the biggest corporate scandals in history has been linked to its former top leader. This paper presents an exploratory study measuring the extent of ethical leadership among youth in Malaysia. Since youth represents one of the most valuable assets in the development of a country, it is pertinent to understand the attributes of these future leaders. Quantitative method was employed and data were collected through questionnaires involving 600 university students from three different universities in Malaysia. The questionnaire was adapted from Ethical Leadership at Work (ELW) instrument containing seven (7) attributes of ethical leadership. The findings revealed that “integrity” scored the highest mean score while “fairness” scored the lowest. However, with a narrow range between the high mean scores, the study also concludes that Malaysian youth embraced various ethical leadership attributes. Since there are limited studies examining leadership components among youth, the current study is among the first to explore ethical leadership attributes among youth in the context of a developing country. Although Malaysia has been bombarded with the 1MDB scandal, the level of ethics embraced by the Malaysian youth should be applauded. In terms of practice, it is important for the youth to be nurtured with these attributes at an early stage. This helps to develop future leaders who are capable to resolve ethical dilemmas when leading the country. The findings of this study provide a guideline to policy makers such as university administrators, in encouraging ethical culture in Malaysia towards a holistic approach in making sure that the country’s economic, social, cultural and environmental targets could be achieved.